The influence of different level of opponents on internal responsesand external loads during small-sided games in soccer - Karel Hůlka; Radim Weisser; Jan Bělka; Pavel Háp (Palacký University Olomouc, 2015)
Background: Small-sided games belong to specific training where exercise intensity can be manipulated mainly by modifying external factors. To ensure suitable usage of small-sided games in practice, we have to know the variables, which could influence internal responses and external loads. Objective: The purpose of this work is to determine the influence of opponents of different levels on internal response and external load during a 4-a-side soccer game. Methods: Twenty physical education and soccer coaching students (age 22.53 ± 1.02 years; body mass index 20.83 ± 2.13 kg ⋅ m-2; peak heart rate 195.26 ± 6.05 beats ⋅ min-1) participated in the study. Heart rate, distance covered, global rate of perceived exertion, and technical demands (passes, shots, steals, turnovers) were monitored. The participants were divided into two higher level teams and two lower level teams according to experts' perfomance ranking. Results: The results showed significantly lower average heart rate achieved by higher level teams in the 4-a-side game against lower level opponents compared to against higher level teams. Then lower level teams reached significantly higher average heart rate in the 4-a-side game against higher level teams than in mutual lower level team 4-a-side game. We found out significantly higher distance covered by lower level teams in 4-a-side game against higher level teams than in lower level teams mutual 4-a-side game. Conclusions: The results of this study demonstrated that the performance level of opponents influence internal and external load of the players. The higher level of opponents increases the work load of lower level teams.